Indonesian students’ engagement in online EFL writing class and their perceptions on teacher feedback - Siti Mafulah; Bambang Yudi Cahyono (Universitas Pendidikan Indonesia, 2023)
Teacher feedback on students’ writing is critical in developing students’ writing performance which is evident from the abundant research on this area. However, little is known about students’ engagement with teacher feedback in an online EFL writing class. Therefore, applying a survey research design, this study aimed to depict how students engaged in an online EFL writing class. It also examined the students’ perceptions on the teacher feedback provision. This study involved 24 Indonesian students taking Paragraph Writing course offered at a university level. The student’s online EFL writing class activities were observed to know their engagement with teacher feedback on their written work. They were also asked to fill in the questionnaire and interviewed to know their perceptions on the feedback. The results showed that students engaged actively in an online EFL classroom. Besides, teacher feedback was seen as a positive practice that was useful to the process the students undergo in EFL writing, leading to improving their writing performance. The findings imply the need for teachers to use an online class as a new setting for teaching writing and in providing feedback on the students’ drafts. The provision of feedback in the online class should take cognitive and affective dimensions into account to cater to knowledge diversity and lower anxiety.